Oil Pollution in the Coastal Waters off Port Dickson, Straits of Malacca - Law, A. T.; Ravinthar, Vellu; Yeong, C. H. (1990)
The petroleum hydrocarbon dist1ibution in the Port Dichson coastal waters was studied over a period of three years from 1986 to 1989. Generally, there was no significant difference (P > 0.05) of hydrocarbon levels in water among the sampling stations on each of the sampling dates. However a pronounced fluctuation was found at different samping dates. Similarly, a pronounced fluctuation of hydrocarbon content in the sediment with different sampling dates was also detected. The mean hydrocarbon level in the water ranged between 14.69ppb and 150.28 ppb, ESSO 'Tapis A crude oil equivalent (or between 0.77 ppb and 7.87 ppb, chrysene equivalent), while for the sediment it ranged between 21. 73 mg/kg and 74.50 mg/kgdry sediment, Esso Tapis A crude oil equivalent (or between 1.12 mg/hgand 3. 90 mg/kgdry sediment, chrysene equivalent). The oil pollution level in the PortDickson coastal waters was comparable or higher than that found in the Exclusive Economic Zone watels off Pahang and Sabah, but was lower than that detected in the Terengganu and Sanl1uak waters. The saUTce of hydrocarbon pollution in the POTt Dichsm~ coastal waters was probably from the open sea and the nearby harbour and oil refineries rather than from land TUn off